Influence of type and concentration of lyoprotectants, storage temperature and storage duration on cell viability and antibacterial activity of freeze-dried lactic acid bacterium, Lactococcus lactis Gh1 - Jawan, Roslina (Taylor & Francis, 2022)
This study was aimed at evaluating the influence of type and concentration of lyoprotectants, storage temperature and storage duration on cell viability and antibacterial activity of Lactococcus lactis Gh1 after drying and during a long-term storage for 120 days. Highest survivability rate after freeze-drying was observed for cells protected in galactose followed by trehalose and peptone. The differences in cell viability among the different types of protective agent and between the concentrations after freeze-drying were not significant. However, significant difference was seen between the protective agents at different concentrations during storage. At high storage temperatures, the number of viable cells decreased for all protective agents and concentrations investigated in this study. Antibacterial activity from L. lactis Gh1 against Listeria monocytogenes ATCC 15313 was in linear correlation with the viable cell counts. Possible formulation of protective agent from this study could be applied in the industrial development of probiotic and bioprotective cultures.